Implemented methods in extension practice for new producers/farmers in organic production - Filipović, Vladimir; Ugrenović, Vladan (Economics of Agriculture, 2010)
Reorientation from conventional to organic and other controlled types of ecological production requires a more systematic approach and the multiple knowledge of different areas encompassed by these types of production. The introduction of organic production represents a multiphase process, where a producer must master technical, technological, economic, legal and ecological aspects of production. The need for services provided by an extensionist in most European countries represents a norm which signifcantly contributes to the increase of the number of certifed producers. In our conditions, such an approach in extension practice has been initiated only recently. To be more precise, in the shape of their planned activities, the expert team of the "Tamiš" Institute, Pančevo has creates a method of extension practice, which was used on the occasion of the introduction of organic production to producers.